Agentive Semiotics as a Methodological Framework for a Pedagogy of Understanding (Global Journal of Human-Social Science, 2025)
This article proposes agentive semiotics as a methodological framework for a pedagogy of understanding that empowers student agency and reconfigures the teaching role From a perspective that conceives meaning as the result of the interaction between agent agenda and context it critiques applicationism the commercial orientation of materials and the uncritical adoption of non-situated models for limiting critical thinking and self-regulation It proposes an analytical model that integrates cognitive affective and situational dimensions promoting the de-automatization of practices the formulation of meaningful questions and the development of rhizomatic lines of flight that open up creative and collective learning possibilities The proposal culminates in strategies to anchor understanding in lived experience and narrative understanding education as a living critical and humanized process capable of transforming both pedagogical practices and the subjectivities that inhabit them
Keywords: agentive semiotics; pedagogy of understanding; student agency; situated models; deautomatization; lines of flight; narrationality